26-13x=-52

Simple and best practice solution for 26-13x=-52 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 26-13x=-52 equation:


Simplifying
26 + -13x = -52

Solving
26 + -13x = -52

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-26' to each side of the equation.
26 + -26 + -13x = -52 + -26

Combine like terms: 26 + -26 = 0
0 + -13x = -52 + -26
-13x = -52 + -26

Combine like terms: -52 + -26 = -78
-13x = -78

Divide each side by '-13'.
x = 6

Simplifying
x = 6

See similar equations:

| 553/48x=265 | | -7=7/8k | | 1.5x+2=20 | | (3c-5)(3c-5)= | | -4(y+2)-6y= | | -5x+47=-31 | | -2(y+6)=y+3-(-2y) | | -180=2x+7(5x-12) | | 2x-6=3x+1-x | | -5h=85 | | 11-(-8x)+5x-(-10)= | | -3a+5+4a=10-26+5 | | 4-28x=-28x-40 | | 7(-1-3k)= | | 5(3x+6y)+4(2x-9y)= | | 28-7x-4=(-7x-7) | | -180=2x+7(5x-2) | | 9(3y+2)=7(4y+7) | | 2/3x-1/2=6 | | -7+2=16 | | 5a+3=-42 | | 18/432 | | Sin(a)=.345 | | 7x(3x^2)+4=0 | | 2p+5r=p | | 70p+30q= | | 5a+3=42 | | -6x-120=-180 | | 4(3x-2)+6=-7(3-2x)+5 | | 5x+1+3x+3=20 | | 5x/9=1/2 | | 1x-4=-1+2x |

Equations solver categories